The Polemic of Coronavirus Open-up Versus Lockdown - Ferdinand Nainggolan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
The pandemic Covid-19 has fueled a crisis democracy around the world as well as Indonesia. The condition of democracy and public/politician/human rights has growth worse. Government of Indonesia has responded that polemic by reducing pandemic cases and give support to the poor one. The number of confirmed Covid-19 positive cases as per July 19, 2021, has risen by 34,257 from the previous day and the total becomes 2,911,733. In the same period, the number of deaths increase 1,338 to 74,920. It has become the government and politicians/public/human right dilemma between controlling the virus and boosting the economy. The fight against pandemic Covid-19 is often framed as a trade-off between public health and the economy. Government aware that implementing a lockdown would require a huge budget, creating a budget deficit that could well exceed the ceiling must be approved by parliament. Government is currently battling the second wave of Covid-19 infections. The delta variants from India have been a major contribution to this second wave as they are more infections. Hospital has shortage of oxygen and beds, and the new patients must place in corridors or tents. Medical workers are tired, and some have become casualties. Lives have been upended and economic activities disrupted, especially to the informal business/workers. Unemployment rate, August 31, 2020, 7,07% while February 28, 2021 is 6,26%. The government of Indonesia has done a lot of effort to handle the Coronavirus, nevertheless public criticism has grown louder in recent months as the dire consequences for health, society, and economy. Some of them are honest but others may have hidden agenda. The game theory is not the only one to measure the optimal solution open-up versus lockdown form Covid-19 polemic. The cost-effectiveness analysis, Bayesien game setting, the strackelberg model are also other tools to measure the optimalization of open-up and lockdown.